Decompressive craniotomy. (30th April 2020) - Groombridge, Christopher; Maini, Amit; Mathew, Joseph; O'Keeffe, Francis; Noonan, Mike; Smit, De Villiers; Fitzgerald, Mark; Tee, Jin
Abstract : An unconscious patient with an extra‐dural haematoma may not survive transfer to a neurosurgical centre for definitive care. This article describes a simple approach to a decompressive craniotomy which may be life‐saving in these patients when a neurosurgeon is not available.